A functional SNP in the FOXP3 gene is associated with an increased risk of developing pre-eclampsia. (18th April 2012) - Davies, P; Ko, S; McCarthy, R; Orsi, N; Zghebeh, H; Walker, J; Simpson, N
Abstract : Introduction: Pre-eclamptic toxaemia (PET) is a common, serious hypertensive disorder of pregnancy. Defective and deficient regulatory T-lymphocytes (Treg) are evident in PET, underlying the hyperinflammatory state. Polymorphisms in FOXP3, a transcription factor that regulates Treg functional characteristics, may be implicated in their dysfunction. This retrospective case-control approach carried out a gene association study of the functional rs2280883 single nucleotide polymorphism (SNP) in PET. Materials and method: Normotensive pregnant women and those with PET were recruited from Leeds Teaching Hospitals. DNA was extracted from their blood samples. Primers were designed and optimised to amplify the rs2280883 flanking regions. The rs2280883 SNP was amplified from the samples, then purified for sequencing. Sanger sequencing genotyped the products with a 3130xl genetic analyser. Statistical analyses using standard 2x2 and chi-square tests were used to determine intergroup differences. Results: In total 138 women were studied (PET=51, normotensive=89). The C (variant) allele frequency was significantly higher in those women with PET vs normotensive controls (45.1% v 29.9%, p=0.01). The genotype distribution was significantly associated with PET favouring carriage of CC + CT genotypes (p=0.049). Discussion: This significant association between the variant C allele of rs2280883 and preeclampsia suggests the FOXP3 gene is involved in immune dysfunction in the emergence and/or progression of PET. Further studies into other genetic variants of FOXP3 and equivalent immunoregulatory genes are indicated to construct a haplotype corresponding to genetic predisposition to PET.